Computational analysis of curved prestressed concrete box-girder bridges using finite element method - Shubhi Ojha; Priyaranjan Pal; P. K. Mehta (Scientific Reports)
Abstract The study employs finite element method to examine the effects of curve angle variations on the behavior of single and double-cell prestressed concrete box-girder bridges. A total of eighty bridge models were examined, featuring a range of curve angles from 0 to 60°, with increments of 12° between each model (0°, 12°, 24°, 36°, 48°, and 60°). The study revealed that bridges with curve angles of 24° or less exhibit minimal impact on forces, suggesting that they can be effectively treated as straight bridges for analytical purposes. The study revealed a marked change in structural response for bridges with curve angles greater than 24°, highlighting the influence of increased curvature on bridge behavior. A comprehensive evaluation was conducted to investigate the influence of changes in curve angles, span lengths, cell numbers, and span–depth ratios on structural forces and deflections under various load types, including dead, live, and prestressed loads. As the curve angle increases, a corresponding decrease in the flexural moment and vertical deflection is observed under prestressed loading conditions. Based on the analysis, it is reasonable to conclude that prestressed concrete box-girder bridges are best suited for applications involving higher curve angles.